2020
DOI: 10.1186/s13244-020-00894-3
|View full text |Cite
|
Sign up to set email alerts
|

MRI characterization of focal liver lesions in non-cirrhotic patients: assessment of added value of gadoxetic acid-enhanced hepatobiliary phase imaging

Abstract: Background To evaluate the added value of the hepatobiliary (HPB) phase in gadoxetic acid-enhanced magnetic resonance imaging (MRI) in characterizing newly discovered indeterminate focal liver lesions in non-cirrhotic patients. Results One-hundred and twenty-five non-cirrhotic patients (median age, 46 years; range, 20–85 years; 100 females) underwent gadoxetic acid-enhanced MRI, including the 20-min delayed HPB phase, for characterization of newly discovered focal liver lesions. Images were independently eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…MRI without intravenous contrast agent may therefore answer the clinical question between benignity and malignancy in some cases. In addition, as Moosavi et al [ 64 ] demonstrated in their study on newly discovered indeterminate focal liver lesions in non-cirrhotic subjects, the information obtained from the HBP does not necessarily modify the diagnosis or the diagnostic confidence. Therefore, in selected cases if the radiologist is confident with the lesion characterization on non-contrast sequences ( e.g.…”
Section: Conventional Mri Features Of Liver Metastasesmentioning
confidence: 96%
“…MRI without intravenous contrast agent may therefore answer the clinical question between benignity and malignancy in some cases. In addition, as Moosavi et al [ 64 ] demonstrated in their study on newly discovered indeterminate focal liver lesions in non-cirrhotic subjects, the information obtained from the HBP does not necessarily modify the diagnosis or the diagnostic confidence. Therefore, in selected cases if the radiologist is confident with the lesion characterization on non-contrast sequences ( e.g.…”
Section: Conventional Mri Features Of Liver Metastasesmentioning
confidence: 96%